2006
DOI: 10.1001/archotol.132.9.934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Type 2 Diabetes Mellitus on Cochlear Structure in Humans

Abstract: To evaluate the effects of type 2 diabetes mellitus on cochlear elements in humans. Design: Comparative study of the histopathologic characteristics of human temporal bones. Setting: Otopathology laboratory in a tertiary academic medical center. Patients: Temporal bones from 18 patients with type 2 diabetes mellitus were divided into 2 groups according to the method of management of diabetes: insulin in 11 patients (mean age, 51.9 years; age range, 44-65 years) and oral hypoglycemic agents in 7 patients (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
125
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 20 publications
6
125
1
4
Order By: Relevance
“…The suggested pathogenesis includes cochlear microangiopathy, hyperglycemia of the cerebrospinal fluid or perilymph, auditory neuropathy and diabetic encephalopathy 8) . Fukushima et al described a diabetesassociated pathology in the cochlea that includes thickened vessels of the stria vascularis, atrophy of the stria vascularis and loss of outer hair cells 9) . Many other studies have reported that diabetes is a risk factor for hearing loss [10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…The suggested pathogenesis includes cochlear microangiopathy, hyperglycemia of the cerebrospinal fluid or perilymph, auditory neuropathy and diabetic encephalopathy 8) . Fukushima et al described a diabetesassociated pathology in the cochlea that includes thickened vessels of the stria vascularis, atrophy of the stria vascularis and loss of outer hair cells 9) . Many other studies have reported that diabetes is a risk factor for hearing loss [10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…[5] However, there is not enough evidence to solidly define diabetes mellitus as a cause of hearing loss. [6] The two important factors seen in diabetics which affect hearing are: Diabetic angiopathy and neuropathy.Diabetes mellitus causes increased rate of triglyceride production due to insulin resistance. There is endothelial proliferation and accumulation of glycoproteins, with thickening of the capillary vessels in basement membranes.…”
Section: Discussionmentioning
confidence: 99%
“…But in HFA the type 2 diabetic individuals showed a significant bilateral mild or moderate degree symmetrical sloping hearing loss with high variability in thresholds. This can be accounted to the fact that atrophy and thickening of blood vessels of stria vascularis in basal turns of cochlea occurs in individuals with type 2 diabetic mellitus [3].…”
Section: Discussionmentioning
confidence: 99%
“…In type 2 DM, walls of blood vessels of stria vascularis were thicker in basal turns in subjects who took oral hypoglycemic agents, walls of blood vessels of stria vascularis and basilar membrane were thicker in basal turns in subjects who were on insulin therapy. Atrophy of stria vascularis of most turns in subjects who were on insulin therapy and the atrophy involved the lower turns in oral hypoglycemic agent subjects [3].…”
Section: Introductionmentioning
confidence: 97%